Numerical modelling of a multi-stage solar still - Jubran, B.; Ahmed, Mirghani Ishak; Ismail, Ahmad Faris; Abakar, Y.A (Pergamon, 2000)
This paper reports the development of a mathematical model to predict the productivity and the thermal characteristics of a multistage solar still with an expansion nozzle and heat recovery in each stage of the still. Furthermore, this model is used to conduct a parametric investigation of the proposed solar still. A cost analysis is performed to shed some light on the potential of utilizing the proposed still for production of drinking water. It was found that making use of an expansion nozzle and heat recovery techniques in the proposed solar still tend to enhance the productivity of the still and the distillation effciency. The daily solar still productivity can be up to 9 kg/m2, and the distillation effciency is 87%. The unit cost for distilled water of this still is $25.6/1000 gallons.